2022
DOI: 10.3390/pr10020390
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Oxide Nanorod-Modified GCE as Sensitive Electrodes for Simultaneous Detection of Hydroquinone and Catechol

Abstract: An electrochemical sensor based on a cobalt oxide nanorod (Co3O4NR) modified glassy carbon electrode (GCE) (Co3O4NR-GCE) was prepared for simultaneous and selective determination of hydroquinone (HQ) and catechol (CT). Surface morphology and crystallinity of Co3O4NR were investigated employing field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) analysis. The structure (16 nm) of the Co3O4 nanorod was observed in the FESEM image. A sharp peak pattern in the XRD survey revealed the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These results indicate that the oxidation process is controlled by diffusion. 46 The regression equation (E pa = 0.78 + 0.063 logv) and regression coefficient (R 2 = 0.99) obtained from the analysis of peak potential (E p ) vs logarithm of scan rate (log v), as shown in Fig. 5c, revealed that the oxidation process was irreversible.…”
Section: Resultsmentioning
confidence: 94%
“…These results indicate that the oxidation process is controlled by diffusion. 46 The regression equation (E pa = 0.78 + 0.063 logv) and regression coefficient (R 2 = 0.99) obtained from the analysis of peak potential (E p ) vs logarithm of scan rate (log v), as shown in Fig. 5c, revealed that the oxidation process was irreversible.…”
Section: Resultsmentioning
confidence: 94%
“…In 1960, cobalt oxide was studied for the first time as a catalyst for the total oxidation of hydrocarbons and carbon monoxide. 60 It was then studied for various applications, such as an active material in electrochromic devices (as it switches from intense brown in the oxidized state (colored state) to green in the reduced state (bleached state)), 27,61 solid-state gas sensors, 62 active and stable heterogeneous catalysts, 63 magnetoresistive devices, 64 as a negative electrode in rechargeable lithium batteries, 42 in water splitting, [65][66][67] as a sensor for determination of nitrite in wastewater, 68,69 acetaminophen detection in biological samples and commercial pharmaceutical preparations, 70 electrode material for the vanadium flow battery (VFB), 71 photoelectrochemical applications (PEC), 72 in the development of latent fingerprints, 73 to detect hydrogen peroxide in the nanomolar concentration range, 74 environmental remediation applications, such as the degradation of dyes, dye waste, and antibiotics, sodium-ion hybrid capacitors (SICs), 75 in diverse catalytic and biomedical applications due to its unique antimicrobial, anticancer, catalytic, antioxidant, antifungal, and enzyme inhibition properties, 76,77 an electrochemical sensor for simultaneous and selective determination of hydroquinone (HQ) and catechol (CT), 78 field effect transistors, 79 solar cells, 80 as a photocatalyst, 81 for anticancer treatment applications 82 and so on. Applications of Co 3 O 4 in various fields are listed in Fig.…”
Section: Applications Of Co 3 Omentioning
confidence: 99%
“…1 Ecosystems have a high level of toxicity of these chemicals. 2 Catechol and its isomers are included as a category of hazardous water contaminants in both the EPA and EU databases. [3][4][5] Due to the similarities in their chemical structures and properties, simultaneous detection of Hq and Cat is difficult.…”
Section: Introductionmentioning
confidence: 99%